Implementation of Massage During the Pandemic as One of the Efforts to Maintain Fitness - Puji Setyaningsih; Arya T Candra; Moh. Agung Setiabudi; Wawan Setiawan; Galih Farhanto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
Massage is an activity of rubbing or massaging certain parts of the human body which aims to improve blood circulation and provide stimulation to relax injured muscles. In massage there are various kinds including beauty massage, health massage, sports massage. In this activity, the massage carried out by students of the PGRI Banyuwangi University is a health massage by means of reflection, massage is carried out on the legs so that it can stimulate nerves and can increase body immunity. It is hoped that with activities, especially the community around the PGRI Banyuwangi University campus, they can get health massage. The method of implementing this activity is 1) the activity preparation stage, 2) the implementation phase includes training on sports and massage activities, 3) the evaluation stage, which is making a final report. The results of the massage activities were quite a lot, the responses from the participants were quite good and they felt comfortable after the massage, the activity process was smooth and orderly.